Tugas, Fungsi dan Bagian Sekretariat DPRD dalam Membantu Tugas Anggota Dewan Perwakilan Rakyat Daerah (DPRD) Kota Palangka Raya - Muhammad Kurniawan; Salsabila Salsabila; Novi Lidiyasari (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research aims to understand the functions and duties of the Secretariat of the Regional People's Representative Council (DPRD) in assisting council members in carrying out their duties. According to the Mayor Regulation Number 34 of 2019, the Secretariat of the DPRD of Palangkaraya City consists of the following divisions: Secretary, General Affairs, Legislation Affairs, Sessions, Public Relations, and Budgeting and Supervision Facilities. Based on Law No. 32 of 2004 and Government Regulation No. 41 of 2007, the Secretariat of the DPRD is considered a